CT and MRI Findings in Cerebral Aspergilloma - Gärtner, Friederike; Forstenpointner, Julia; Ertl-Wagner, Birgit; Hooshmand, Babak; Riedel, Christian; Jansen, Olav (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose Invasive aspergillosis usually affects immunocompromised patients. It carries a high risk of morbidity and mortality and usually has a nonspecific clinical presentation. Early diagnosis is essential in order to start effective treatment and improve clinical outcome.Materials and Methods In a retrospective search of the PACS databases from two medical centers, we identified 9 patients with histologically proven cerebral aspergilloma. We systematically analyzed CT and MRI imaging findings to identify typical imaging appearances of cerebral aspergilloma.Results CT did not show a typical appearance of the aspergillomas. In 100 % (9/9) there was a rim-attenuated diffusion restriction on MRI imaging. Multiple hypointense layers in the aspergillus wall, especially on the internal side, were detected in 100 % on T2-weighted imaging (9/9). Aspergillomas were T1-hypointense in 66 % of cases (6/9) and partly T1-hyperintense in 33 % (3/9). In 78 % (7/9) of cases, a rim-attenuated diffusion restriction was detected after contrast agent application.Conclusion Nine cases were identified. Whereas CT features were less typical, we observed the following imaging features on MRI: A strong, rim-attenuated diffusion restriction (9/9); onion layer-like hypointense zones, in particular in the innermost part of the abscess wall on T2-weighted images (9/9). Enhancement of the lesion border was present in the majority of the cases (7/9).Key points Citation Format
Keywords: aspergillosis; brain; mr imaging